EFFECT OF LEADERSHIP AND WORKLOAD ON WORK MOTIVATION AND EMPLOYEES PERFORMANCE PT. BANK RIAU KEPRI PEKANBARU BRANCH - Layla Hafni; Ahmad Himawan; Surya Safari SD; Farhan Firdaus (International Conference on Business Management and Accounting, 2022)
This study aims to determine and analyze the influence of leadership and workload on work motivation and employee performance at Bank Riau Kepri Pekanbaru Branch. This research is a quantitative research by distributing questionnaires to respondents. The sample used is 71 people. The sampling technique used is simple random sampling from 190 populations. Data processing uses the Structural Equation Modeling (SEM) method with the SmartPLS application. The results of this study indicate that leadership, workload and motivation have a positive and insignificant effect on performance but leadership has a positive and significant effect on job satisfaction and workload has a significant effect on motivation. Meanwhile, the indirect effect of leadership and workload on employee performance through work motivation is not significant. Suggestions for this research is that employees should be challenged to be creative and think critically to be able to innovate in completing their work. Leaders need to ensure that the work carried out by employees is in accordance with the Standard Operating Procedures and job descriptions, and it is better not to allow employees to hold concurrent positions. Leaders must also always be open to new things, including technology and digital developments to be able to help ease the work of employees in providing the best service for customers. In addition, leaders and management need to maintain this condition so that employees feel that their place of work is their second home so that they feel safe and comfortable at work. And lastly, it is necessary to improve employee performance through continuous education and training so that their work results are in accordance with the standards set and can become a reference for their fellow colleagues.